Aerobic energy system, strength and glutamine supplementation consequences in handball players - Sajedi, H.; Salari, N.; Bas, M.; Bayram, M. (Sport Science - International Scientific Journal of Kinesiology, 2016)
The aim of this study investigated the effects of glutamine supplementation on strength, aerobic energy system. Handball players (n=40) volunteered for this study. Weight and height of the players were measured and the age range was between 17-24 years old (20.7±4.3). The Experimental Group (n=20) was given glutamine treatment of 0.3g/kg/day of glutamine for a period of six weeks and the Control Group (n=20) had no treatment. Each participant performed the Cooper test and strength test. At the end was measured the blood glutamine concentration. There was a significant effect (p<0.05) of the supplementation on VO2max. The glutamine supplement had significant effects (p<0.05) on the strength under post-test condition. Blood glutamine analysis showed modification effects of glutamine consumption the on blood glutamine decreasing. The results concluded a significant effect of glutamine supplementation on VO2max, strength and blood glutamine.